Development of the Flipbook e-module with a Scientific Approach Problem Based Learning in Improving Students' Abstract Skills - Sri Asnawati; Dian Permana Putri; Aan Anisah, Aan Anisah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2023)
The urgency of this research is to help accelerate the implementation of new learning paradigms by meeting the need for learning innovation by using technology to improve students' abstract skills. The aim of this research is to design and analyze the validity, practicality and effectiveness of the Accounting flipbook e-module as well as improving students' abstract skills through a scientific approach combined with problem-based learning methods (Problem Based Learning). The research method used is the R&D method using the 4D development model, namely Define, Design, Development and Dissemination. This research was only carried out until the development stage, the dissemination stage was not carried out due to time constraints. Research data collection techniques are in the form of questionnaires such as validation sheets, questionnaires, concept understanding ability tests and documentation. The data analysis technique used is the percentage descriptive technique, namely changing quantitative data into percentage form, then interpreting it using qualitative sentences. The research results obtained include the results of validation of the design of teaching materials in the form of an Accounting flipbook e-module which is in the